A Medal for Benny Movie Still - Paramount Pictures:::Creator::::::::::::
Lolita Sierra (Dorothy Lamour) and Joe Morales (Arturo de Cordova) in the Paramount Pictures 1945 production of "A Medal for Benny.' According to caption, the production company was giving these two an opportunity to show their talents with this movie.